Global longitudinal strain and quantitative sensory testing in pre-symptomatic patients with mutation for transthyretin amyloidosis. (3rd October 2022) - Canciello, G; Tozza, S; Lombardi, R; Nolano, M; Todde, G; Severi, D; Borrelli, F; Acampa, W; Esposito, G; Manganelli, F; Losi, M A
Abstract: Background: Hereditary transthyretin (ATTRv) amyloidosis is a rare, autosomal dominant, and devastating disease. If untreated, the disease is fatal within 4–15 years from onset. Thus, diagnosis in the early stages of ATTRv amyloidosis is crucial to start treatment and to prevent or delay disease progression. However, the diagnosis of symptomatic ATTRv amyloidosis in TTR gene mutation carriers may be challenging. Purpose: We aimed identifying early indexes of cardiac and/or neurological involvement in pre-symptomatic subjects (carriers) harboring a TTR gene mutation. Methods: Eight TTR-mutation carriers (mean age 51±9 years, 5 males) constituted the study populations. Mutations identified were: Val30Met in 4, and Phe64Leu in the remaining 4 patients. Patients underwent tactile and thermal quantitative sensory testing (QST), 99mTc-labeled bisphosphonate (HMDP) scintigraphy with the evaluation of Perugini score, and comprehensive echocardiogram with evaluation of global longitudinal strain (GLS). Results: Table 1 reports results in overall patients. PADO indicates predicted age of disease onset. MWT indicates maximal wall thickness at echocardiography. There was a strong and inverse correlation between the °C degree at HPT and GLS (r=−0.790; p=0.02, demonstrating that a worse HPT corresponded a better GLS (Figure 1). Conclusion: GLS and QST findings support an early involvement of heart and small nerve fibers even many years before the PADO. Interestingly, cardiac impairment seems to not parallel that of small nerve fibers. An inhomogeneous accumulation of fibrils, as well possible different pathophysiological mechanisms in heart and nerve fibers, might result in a variable organ impairment at least in the earliest stage of disease. Our observation needs to be tested in a wider population with such a rare disease. Funding Acknowledgement: Type of funding sources: None.